Análisis jurídico de los efectos de la acusación particular en el proceso penal ecuatoriano - López Cruz, Karla Alejandra (2023)
The present research work entitled 'LEGAL ANALYSIS OF THE EFFECTS OF THE PRIVATE ACCUSATION IN THE ECUADORIAN CRIMINAL PROCESS', It was based on the fact that the legal concept of the private prosecution has undergone a substantial change in the Ecuadorian criminal process since the current Comprehensive Organic Criminal Code has granted the status of procedural subject to the victim, which implies that the protection of his rights are fully guaranteed even if no private accusation has been presented and it is for that reason that it was It is necessary to ask ourselves the following question: Determine the effectiveness of the legal effects of the Private Accusation in the Ecuadorian criminal process, through the study of criminal regulations, and the analysis of cases in which private accusations have been presented, in criminal proceedings in Ecuador, in order to analyze if its application in favor of the rights of the victim within the Ecuadorian criminal process is effective. For this reason, in order to solve the stated objective, the qualitative legal method was obtained because with this method it was distinguished to describe the quality of the phenomenon, that is, the effects of the Private Accusation were analyzed, for which interviews were conducted with three Judges. , three Prosecutors and three Lawyers since the above increased, due to the exercise of their profession, they can provide relevant information to the investigation, in the same way the analysis of five particular cases was carried out where it was determined what was the proceeding of the accuser in each specific case, concluding that the implementation of the private accusation is indeed effective as long as it is carried out properly.